2003
DOI: 10.1002/cem.825
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multivariate analysis of cockle phenomena

Abstract: The phenomena called cockle are small wrinkles on the paper surface that appear during paper production. This condition poses significant economic and operability problems in the production of magazine paper, as it deteriorates the printabilty of the paper. There are many and varied sources that can lead to cockle, and their detection is often very complicated. In this work a multivariate hierarchical approach is proposed to analyze the cause of cockle. The hierarchy has two levels, the first of which is a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Outliers were identified graphically by plotting principal components analysis (PCA) and PLS scores [13,14]; newer robust multivariate methods of outlier identification are proposed by Hoo et al [15]. The obtained results were analyzed together with the IPB process specialists who suggested that only the pH outlier data collected on 6 April 1997 should not be used to construct the models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outliers were identified graphically by plotting principal components analysis (PCA) and PLS scores [13,14]; newer robust multivariate methods of outlier identification are proposed by Hoo et al [15]. The obtained results were analyzed together with the IPB process specialists who suggested that only the pH outlier data collected on 6 April 1997 should not be used to construct the models.…”
Section: Methodsmentioning
confidence: 99%
“…Only the variable color does not seem to be important to the PLS model. For problems with larger dimensionality, the use of specific approaches for identification of variable importance [14] is essential.…”
Section: Modeling Data Setmentioning
confidence: 99%
“…For semi-supervised and unsupervised techniques, true and false positives (or false alarms) are also assessed [26,43,65,126] . For regression based tensor models and tensor forecasting methods, prediction error metrics such as root mean square error (RMSE) or mean absolute error (MAE) is normally used [50,59,71,90,92,124,136,154] . Detection delay has also been exploited in some works [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Outliers were identified graphically by plotting principal components analysis (PCA) and PLS scores [13,14]; newer robust multivariate methods of outlier identification are proposed by Hoo et al [15]. The obtained results were analyzed together with the IPB process specialists who suggested that only the pH outlier data collected on 6 April 1997 should not be used to construct the models.…”
Section: Methodsmentioning
confidence: 99%